An outbreak of severe coagulopathy from synthetic cannabinoids tainted with Long-Acting anticoagulant rodenticides. (2nd August 2020) - Devgun, Jason M.; Rasin, Arkady; Kim, Theresa; Mycyk, Mark B.; Bryant, Sean M.; Wahl, Michael S.; DesLauriers, Carol; Navon, Livia; Moritz, Erin D.; Thompson, Trevonne M.; Swoboda, Henry D.; Lu, Jenny; et al.
Abstract: Objective: To describe a large regional poison center's experience managing an outbreak of long-acting anticoagulant rodenticide (LAAR) poisoning associated with synthetic cannabinoid (SC) use. Methods: This is a retrospective review of exposures reported to the Illinois Poison Center between March 10 and August 1, 2018. All cases coded as exposure to Δ9-tetrahydrocannabinol homologs were identified. Patients with suspected SC use, positive LAAR testing, and coagulopathy (signs or symptoms of bleeding or international normalized ratio [INR] > 2) were included. If confirmatory LAAR testing was performed and resulted as negative, the patient was excluded from this analysis. In the absence of LAAR testing, patients with suspected SC use, an INR >2, and no alternative explanation of coagulopathy were included. Suspected SC use was defined as use suspected by a member of the treating team or reported by the patient. Presenting signs and symptoms, laboratory findings, management, healthcare utilization, outcomes, and disposition of patients affected by this outbreak were reported. Results: One hundred seventy-eight cases met inclusion criteria. Most patients were male (73%) and young to middle-aged (median age 32, IQR 25–40). Most presented to hospitals in Peoria (35%) and Cook (31%) counties. Median hospitalization was three days (IQR 2–4). Eighty-eight percent of patients presented with an INR >10. Eighteen cases had qualitative anticoagulant testing, all of which were positive for brodifacoum. Other identified LAARs included difenacoum (10/18) and bromadiolone (1/18). Sixty-three percent of patients had back, flank or abdominal pain; 70% of patients presented with hematuria. One hundred six cases received IV vitamin K1 ; no adverse or anaphylactoid reactions were reported. Forty-one (22%) patients left AMA. Thirty-eight patients (21%) were re-hospitalized during the study period. Patients leaving AMA were 1.6 times more likely to be re-hospitalized than patients with other dispositions. Intracranial hemorrhage, present in 3% of total cases, was present in 4 of 5 fatalities. Conclusions: We describe an outbreak of multiple LAARs contaminating SCs. Patients presented with bleeding from varied sites, often required blood products, factor replacement, and high dose vitamin K1 for stabilization.